Federal nutrition programs and childhood obesity: Inside the black box - Manan Roy; Daniel L. Millimet; Rusty Tchernis (Institute for the Study of Labor (IZA), 2010)
In response to the dramatic rise in childhood obesity, particularly among low income individuals, federal nutrition assistance programs have come under scrutiny. However, the vast majority of this research focuses on the direct relationship between these programs and child health, while little is known about the mechanisms by which such relationships arise. Using the 2007 American Time Use Survey and the Eating and Health Module, we explore differences in time use across families that participate in the Supplemental Nutriation Assistance Program (SNAP), the School Breakfast Program (SBP), and the National School Lunch Program (NSLP) to better understand behavioral differences across participants and non-participants. These differences have important implications for future research and policy.
Keywords: C31; H51; I18; I28; 330; School Breakfast Program; National School Lunch Program; Supplemental Nutrition Assistance Program; time use; program evaluation